SISTEM PERTANAMAN ORGANIK “SOIL PONIK” MODEL HORIZONTAL MELALUI PENERAPAN PUPUK ORGANIK CAIR PADA TANAMAN SAWI (Brassica rapa L.) - Musdalifa Musdalifa; Umrah Umrah; Asri Pirade Paserang (Biocelebes, 2020)
Liquid organic ferilizer is fertilizer produced from organic materials, such as weathering food scraps, animals and human organic waste that has been processed, can be solid or liquid. Liquid organic fertilizer contains carbon at 7,1% and a nitrogen content of 3,3%. This studi aims to determine the effect of the horizontal “soil organic” planting system through the application of mustard plants (B. rapa L.) and find out at what dosage the optimum liquid organic fertilizer for the of mustard plants. This studi was designed in a randomized block design with 11 treatments and 3 replication. Treatment arrangement: P0 (whitout fertilizer), P1 (1 mil liquid organic fertilizer), P2 (2 mil), P3 (3 mil), P4 (4 mil), P5 (5 mil), P6 (6 mil), P7 (7 mil), P8 (8 mil), P9 (9 mil) and P10 (10 mil). The result of the study showed the best growth for plant height in P2 with a value of 11,78, for the number of leaves in P2 with a value of 11,20, for the fresh weight of roots in P0 with a value of 2,45, for root dry weight at P6 with a value of 1,1, for plant wet weight in P5 with a value of 15.36 and for plant dry weight in P5 with a value of 1,65.